Vibrational energy flow in structures - Palmer, James Dirk (1994)
This investigation explores the use of an approximate energy flow approach to provide a global modelling tool capable of predicting the pattern and level of vibrational energy flow in complex structures. The modelling approach is based on a differential control volume formulation which, by virtue of its simplified nature, describes the flow of mechanical energy within a structural component in a manner analogous to the flow of thermal energy in heat conduction problems. For complex structures the approach can be implemented using existing finite element software through an analogy between the thermal and vibrational systems.